Alcohol-related problems among college and university students in Norway: extent of the problem. Issue 4 (June 2021) - Heradstveit, Ove; Skogen, Jens Christoffer; Brunborg, Geir Scott; Lønning, Kari Jussi; Sivertsen, Børge
Aims: The aim of the current study was to provide estimates of the distribution of alcohol-related problems in a large sample of college and university students. We also sought to examine trends in the distribution of alcohol-related problems from 2010 to 2018. Methods: Data stem from a recent national health survey from 2018 for higher education in Norway (the SHoT study) in which 50, 054 full-time students (69.1% women; 30.9% men) aged 18–35 years participated. The Alcohol Use Disorders Identification Test (AUDIT) was used to assess potential alcohol-related problems. Data on demographic characteristics were also collected. Results: More than half of the male students (52.8%) and 4 out of 10 of the female students (40.1%) reported risky, harmful or dependent alcohol use. Compared to women, men had an increased risk of risky alcohol use (relative risk ratio (RRR) = 1.57), harmful alcohol use (RRR = 2.45) and dependent alcohol use (RRR = 2.73). Younger students had higher rates of risky and harmful alcohol use compared with older students, while rates of dependent alcohol use were similar across the age span. Several demographic variables were associated with alcohol use. The trend analyses revealed that the rates of risky, harmful and dependent alcohol use, as well as mean AUDIT scores, among the students have remained relatively stable over the past 8 years. Conclusions: Alcohol use remains an important health concern among Norwegian college and university students, and the present study confirms the high rates of alcohol-related problems, and the need to address the issue within this population.